The Business Crime In The Use of Foreign Labor in Indonesia Perspective of People Smuggling - Rizkan Zulyadi; Mahmud Mulyadi (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2025)
The purpose of this study is to analyze the legal regulations in Indonesia regarding the use of foreign workers in connection with the criminal offense of human smuggling, as well as to examine the enforcement of the law against business actors who illegally employ foreign workers from the perspective of human smuggling. This research uses a normative legal approach by reviewing legislation, court decisions, and legal doctrines through statutory, case, and conceptual approaches, along with library research techniques and descriptive-analytical qualitative data analysis. The findings indicate that legal regulations in Indonesia concerning the use of foreign workers linked to human smuggling are covered by various laws such as the Manpower Act, the Immigration Act, and the Anti-Trafficking Law (UU TPPO), but remain partial and do not explicitly regulate smuggling in the context of corporations as perpetrators, which hinders legal enforcement. Law enforcement against such business crimes still faces multiple obstacles, such as weak legal frameworks, operational modes disguised as legal recruitment, limited understanding among law enforcement officials regarding transnational crimes, and the suboptimal implementation of corporate criminal liability, resulting in many cases ending only in administrative sanctions such as deportation, without significant deterrent effects